Genetic Diversity Assessment of Sweetpotato Germplasm in China Using InDel Markers - Lukuan Zhao; Zhanghua Qi; Shizhuo Xiao; Fen Tang; Yang Liu; Yitong Deng; Xibin Dai; Zhilin Zhou; Wenjun Ou; Qinghe Cao (Agronomy, 2022)
Sweetpotato (Ipomoea batatas (L.) Lam.), whose roots are rich in starch, is widely grown around the world and plays a prominent role in ensuring food security. At present, there are no reports on the genetic diversity of sweetpotato germplasm revealed by InDel markers. In this study, we developed a set of 30 InDel markers to evaluate the genetic diversity and relationships of 240 accessions, comprising 77 landraces, 80 introduced accessions, 82 improved varieties released in China, and a diploid wild relative Ipomoea trifida. A total of 94 reliable loci were obtained, with a mean of 3.13 loci per primer, and the PIC value ranged from 0.143 to 0.821. The whole population could be divided into three sub-populations according to a structure analysis based on the Bayesian model, which was consistent with the results of principal component analysis (PCA). A neighbor-joining tree was constructed based on Nei’s genetic distance ranging from 0 to 0.556 and discriminated the panel of the population into three main groups (Ⅰ, Ⅱ, Ⅲ). Group Ⅲ was further split into seven subgroups (ⅢA–ⅢG). The clustering pattern of the 240 accessions was unrelated to their geographic origins. Most of the accessions, whether landraces, improved varieties released in China or introduced germplasm, were mixed, which revealed the high level of genetic similarity among accessions from different regions. There was little difference in the level of genetic diversity between landraces and improved varieties, which was probably due to the exchange and utilization of accessions from different regions. More efforts should be made to collect and utilize sweetpotato germplasm resources and further broaden the genetic basis of sweetpotato cultivars.